MHD free convection in a wavy open porous tall cavity filled with nanofluids under an effect of corner heater. (December 2016) - Sheremet, M.A.; Oztop, H.F.; Pop, I.; Al-Salem, K.
Highlights: Numerical analysis of MHD natural convection in a wavy open porous cavity filled with a Cu–water nanofluid has been made. Magnetic field is the main effective parameter on natural convection. An increase in the Hartmann number leads to a reduction of convective flow rate. Abstract: A numerical analysis of MHD natural convection in a wavy open porous tall cavity filled with a Cu–water nanofluid in the presence of an isothermal corner heater has been carried out. The cavity is cooled from the left wavy wall and heated from the right bottom corner while the bottom wall is adiabatic. Uniform magnetic field affects the heat transfer and fluid flow with an inclination angle to the axis x ¯ . Mathematical model formulated using the single-phase nanofluid approach in dimensionless variables stream function, vorticity and temperature has been solved by finite difference method of the second order accuracy in a wide range of governing parameters: Rayleigh number ( Ra = 100–1000), Hartmann number ( Ha = 0–100), inclination angle of the magnetic field ( γ = 0– π ) and solid volume fraction parameter of nanoparticles ( φ = 0.0–0.05). Main efforts have been focused on the effects of these parameters on the fluid flow and heat transfer inside the cavity. Numerical results have been presented in the form of streamlines, isotherms and average Nusselt numbers. It has been found heat transfer enhancement with Rayleigh number and heat transfer reduction with Hartmann number, while magnetic field inclination angle leads to non-monotonic changes of the heat transfer rate.